2021
DOI: 10.1002/pmrj.12581
|View full text |Cite
|
Sign up to set email alerts
|

Individual and cumulative health afflictions are associated with greater impairment in physical and mental function in former professional American style football players

Abstract: Background Former American style football players (ASF players) have recognized health concerns associated with prior sport participation. It remains unknown whether categorizations of current health conditions, referred to in this report as afflictions (conceptually framed as neurocognitive, cardiovascular, cardiometabolic, sleep apnea, and chronic pain) are associated with physical and mental function. Objective To evaluate the association of afflictions to physical and mental function. It was hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…After selection based on the pertinence and relevance to the topic of the review, 11,191 records were excluded, leaving 47 articles meeting the selection criteria. The full texts of the selected articles were assessed for inclusion, and 30 further articles were excluded as 3 were case reports [17,19,45], 1 review [46], 1 reported participation in sports as a leisure activity [47] 2 reported data only on an overall measure of physical activity [48,49] 2 included only athletes who had ≥ 1 head/brain injury [50,51] 8 did not report any measure of risk of NDs and/or NCDs [20,[52][53][54][55][56][57][58] and 13 were already included in the 2016 review [59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 99%
“…After selection based on the pertinence and relevance to the topic of the review, 11,191 records were excluded, leaving 47 articles meeting the selection criteria. The full texts of the selected articles were assessed for inclusion, and 30 further articles were excluded as 3 were case reports [17,19,45], 1 review [46], 1 reported participation in sports as a leisure activity [47] 2 reported data only on an overall measure of physical activity [48,49] 2 included only athletes who had ≥ 1 head/brain injury [50,51] 8 did not report any measure of risk of NDs and/or NCDs [20,[52][53][54][55][56][57][58] and 13 were already included in the 2016 review [59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 99%
“…Research from the Football Player Health Study has explored multiple aspects of health and impairments that are observed in former ASF players that include neurocognitive impairments and other domains, including cardiometabolic, sleep apnea, and chronic pain. For example, using questionnaires in more than 4100 former players, we have observed that multiple health domains may be associated with impairments in physical and mental health (22). History of concussion may be associated with depression, anxiety, and impaired quality of life in this cohort (23).…”
Section: Discussionmentioning
confidence: 99%
“…For example, numerous studies have independently reported relatively high rates of these modifiable risk factors in former professional American football players, including hypertension and prehypertension (64.5%), excessive alcohol use, and obesity/body mass index (BMI) > 30 (52%). 10,11 Conversely, lower rates of select modifiable risk factors have also been reported within former professional American football players (e.g., lower rates of impaired fasting glucose, cigarette smoking, and sedentary lifestyle). 11,12 While cumulative risk scores have the potential to comprehensively quantify risk of adverse long-term outcomes, history of TBI/head trauma has not been incorporated as part of the overall weighted risk calculation to date.…”
Section: Introductionmentioning
confidence: 98%
“…Evidence suggests that other modifiable risk factors may play a significant role in risk of neurodegenerative disease in former elite‐level contact sport athletes and that a more comprehensive approach is needed to truly understand and address the risk of long‐term adverse outcomes later in life. For example, numerous studies have independently reported relatively high rates of these modifiable risk factors in former professional American football players, including hypertension and prehypertension (64.5%), excessive alcohol use, and obesity/body mass index (BMI) > 30 (52%) 10,11 . Conversely, lower rates of select modifiable risk factors have also been reported within former professional American football players (e.g., lower rates of impaired fasting glucose, cigarette smoking, and sedentary lifestyle) 11,12 …”
Section: Introductionmentioning
confidence: 99%